Crop response to climate change in southern Africa: A comprehensive review - (:unkn) unknown (My University, 2013)
Concern over future food security in southern Africa has led to various studies that assess the impact of climate change on crops in the region. The results vary according to applied methods and tools. This study reviewed and consolidated results from 19 recent studies which quantitatively project the impact of climate change on crops for the 21st century in southern Africa. Results were assessed according to crop modelling techniques, which included process-based, statistical and economic (Ricardian) modelling. Studies were assessed for their reporting and recommendations concerning adaptation and CO2 fertilisation. Results suggest that the aggregate impact of climate change on crops in southern Africa will be negative. Maize yields are projected to decline on average by 18%. The collective impact of climate change on all crop yields shows a median decline of − 11% and − 14% respectively under process-based and statistical methodologies. Median impacts show declining crop yields through the 21st century. No significant change in the near future, − 18% for the mid century and − 30% for late century. GCM driven Ricardian projections are highly variable. However, uniform climate scenarios project a median revenue decline. Notwithstanding the challenges of such a review; lack of data, bias towards reported methods and tools, uncertainty, scale etc., results indicate that climate change may impact southern African crops in important ways thereby making adaptation essential. Adaptation and CO2 fertilisation could potentially moderate the negative impacts of climate change. This implies a need for studies into future adaptation that consider CO2 fertilisation.
Keywords: African Research